Izzivi rehabilitacijske zdravstvene nege v času pandemije COVID-19 - Kotar, Viki (Rehabilitacija (Ljubljana), 2021)
The largest burden of the coronavirus disease epidemic falls on health care professionals. Nursing staff is already overstretched, and the pandemic has pushed them to their limit. Their main challenged in the COVID-19 era are permanent wearing of protective gear, required caution when dealing with all patients, adapting to organisational changes "red" and "grey zone"), prolonged working hours, fear of expose to the virus and hazard for themselves and their families, inability to assist their children with on-line education, and lack of time for themselves, lunch, sleep and rest. We still do not know for how long we will be exposed to the new virus and what the dynamic of the pandemic will be. We must therefore carefully plan the measures within the central co-ordination team and further within each rehabilitation team, and co-operate with each other at all levels.
Keywords: COVID-19; nevarnosti pri delu; nursing; obremenitve; occupational hazards; organizacija dela; Rehabilitation Nursing; strain; stres; stress; work organisation; zdravstvena nega